Dinamika Penghidupan Pekerja Sektor Informal : Analisis Kebutuhan Ekonomi, Kerentanan Risiko, dan Adaptasi Spiritual Juru Parkir di Kawasan Pasar Bojong Bekasi - Ayu, Asti Laras; Batubara, Noor Azida; Ma’arif, Fauzan Abdul Hafidzh; Sa’adah, Alvina Lailatus; Zahidah, Shofiyah Rahmah; Andiani, Diana; Maulida, Neneng Nur (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The everyday experiences of adolescents working as parking attendants in Bojong Market illustrate how informal workers navigate economic uncertainty in urban public spaces. This study examines how economic pressures, work-related risks, and religious beliefs intersect in shaping their daily lives and coping strategies. Employing a qualitative case study design, data were obtained through direct observation and in-depth interviews with parking attendants operating in the Bojong Market area, Bekasi. The findings indicate that economic necessity remains the primary motivation for engaging in informal work, while irregular income patterns contribute to ongoing financial insecurity. In addition, participants are frequently exposed to occupational risks such as interpersonal conflict, traffic-related accidents, and negative social labeling. Amid these challenges, religious beliefs play a significant role in sustaining emotional endurance and personal meaning. Although economic demands often limit the consistent performance of formal religious practices such as daily prayers, values related to Tawakal (trust in God) and Rezeki (divinely granted livelihood) function as important sources of resilience. These beliefs help individuals rationalize uncertainty, affirm the legitimacy of their work, and preserve optimism. This study offers insight into the ways informal workers integrate spiritual understanding into their strategies for resilience and identity formation under conditions of economic vulnerability.